A Dosis Pupuk Mashitam Dan Pupuk Petro Biofertil Terhadap Pertumbuhan Dan Produksi Tanaman Kacang Tanah (Arachis hypogeae L.) Varietas Jerapah - pamuji setyo; Ayyul Fari Qainy Rikza; M Cholil Mahfud (JURNAL ILMIAH AGRINECA, 2023)
Peanut (Arachis hypogeae L.) is a legume plant that has high nutritional value. In Indonesia, peanuts as a food source have the potential to be developed. The problem in the peanut farming business is that its production is still low. One of the efforts to increase peanut production is by proper fertilization. The continuous use of inorganic fertilizers causes land damage, so it is necessary to implement a sustainable agricultural system. The use of Mashitam organic fertilizer combined with Petro Biofertil biofertilizer is expected to increase peanut production and can be an alternative in reducing the use of inorganic fertilizers. This study aims to explain the effect of giving a dose of organic Mashitam and Petro Biofertil biofertilizers on the growth and production of peanuts. This study used a factorial randomized block design (RAK) with 2 factors and 3 replications. The first factor is the dose of Mashitam fertilizer with 3 levels, namely 300 kg/ha; 400 kg/ha; 500 kg/ha and the second factor is the dosage of Petro Biofertil fertilizer with 4 levels, namely 50 kg/ha; 75 kg/ha; 100 kg/ha; and 125 kg/ha which was repeated 3 times. The results of this study showed that there was a significant interaction in the treatment of giving Mashitam fertilizer and Petro Biofertil fertilizer on the variables: dry weight of 100 peanuts, after the DMRT 5% test showed that the treatment that had the highest average was M2P2 (Masitam fertilizer 400 kg/ha and Petro Biofertil fertilizer 75 kg/ha), while the efficient treatment is M1P3 (Mashitam fertilizer 300 kg/ha and Petro Biofertil fertilizer 100 kg/ha). In the single treatment, the dosage of Mashitam and Petro Biofertil fertilizers on the observed variables of plant height, number of leaves, stem diameter, and fresh weight of pods/plant samples at all observation ages showed no significant difference after further testing with the 5% BNT test. Keywords: Peanut, Petro Biofertil Biofertilizer, Mashitam Organic Fertilizer